A multidisciplinary approach to accidental inhalational ammonia injury: A case report. (October 2022) - Pangeni, Raju Prasad; Timilsina, Bibek; Oli, Prakash Raj; Khadka, Sulochana; Regmi, Pradeep Raj
Abstract: Introduction: Ammonia is a highly toxic irritant gas, and its toxicity usually occurs from occupational exposure. Most are unintentional toxicity. It causes tissue damage via exothermic reaction with body tissues causing liquefactive necrosis. Presentation depends on the level and duration of exposure. Management is supportive and its antidote is not available yet. Presentation of case: We report a case of a 22-year-old male with accidental workplace exposure from coolant damage and leakage. He had altered mental status with visible injury to the nasal cavity, and ulcerated laryngeal mucosa with asymmetric vocal cords on bronchoscopy. Computed tomography showed right lower lobe consolidations. A muti-disciplinary approach and prompt management with respiratory support along with inhaled steroids and bronchodilators, antibiotics, electrolyte replacement, analgesics, and supportive eye and oral treatments were initiated. He had to be managed with a high-flow nasal cannula with subsequent tapering of the oxygen supplementation with titration. Discussion: Inhalation injury due to ammonia toxicity can have varied presentations from mild to severe life-threatening respiratory distress and neurological deterioration. Complications can range from upper airway edema to pulmonary edema. Most of these are usual findings except for the presence of pneumothorax. It could be due to the pre-existing lung status or oxygen therapy but the literature is inadequate. Conclusion: Ammonia inhalational injury may be associated with pneumothorax. It is important to have a multi-disciplinary approach and in-hospital management of ammonia toxicity as well as to raise awareness regarding the work environment and timely recognition of the possible occupational health hazards. Highlights: Pneumothorax in a case of inhalation ammonia injury. Early recognition and a multispecialty approach are vital for the outcome of the toxicity. Awareness of occupational safety measures in the workplace can help minimize the associated health hazards.